Subsidizing education in the economic periphery: Another pitfall or regional policies? - Jens Südekum (Hamburg Institute of International Economics (HWWA), 2002)
One of the most prominent instruments of regional policy is to foster education and human capital formation in economically lagging regions. However, regional policy of this type can actually hurt instead of help the poor areas. The reason is that individual geographical mobility increases with the personal skill level. Through education subsidies, particularly if targeted on relatively high skilled workers, individuals can cross some threshold level of qualification beyond which emigration accrues. Regional policies then result in a human capital flight harmful to individuals remaining in the economic periphery. This fatal result does not hold for such policies that foster basic education and focus on the relatively low skilled.
Keywords: F4; R1; H3; 330; Regional Policy; Education Subsidies; Human Capital; Labour Mobility; European Union; Regionalpolitik; Bildungspolitik; Subvention; Bildungsinvestition; Brain Drain; Kern-Peripherie-Beziehung; Theorie